Just Hit Send: An Analysis of Activist Themed Email Forwards - Whiteman, Ellen (Atlantis, 2008)
This paper examines feminist identities and relationships to online activism. "Cyberjunk" feeds a need for activism in busy women's lives and allows a construction of identity for themselves/ourselves as feminist activists without having to put a body, or perhaps more importantly, valuable time on the line.